A compact formulation for constant velocity joint kinematics. (March 2018) - Cardozo, William Schroeder; Weber, Hans Ingo
Highlights: Compact method to analyze the constant velocity joint kinematics (CVJ). The CVJ model requires only one rotation around the Euler vector defined in a plane. Direct method to calculate the position of the spheres for two race track shapes. The proposed compact kinematics model leads to a more compact dynamic model of the CVJ. Abstract: This work presents a compact method to analyze the constant velocity joint (CVJ) kinematics. Almost every front-wheel drive cars have four CVJs in the front axle. In the literature, general purpose multi-body dynamics software gives the full dynamics and force analysis through numerical simulations of CVJs. If the CVJ is part of a more complex system, the general purpose software requires too much computational effort. The modeling of a CVJ as a double cardan offers a bypass to this limitation using three sequential rotations around orthogonal axes, which lead from the input axis to the output axis of the joint. In this work, the CVJ model requires only one rotation around the Euler vector defined in a plane. A physical explanation for this single rotation is presented. A kinematic analysis is presented with focus on the output axis embarked angular velocity. A direct method to calculate the position of the spheres for two race track shapes is proposed. The results section presents the movement visualization of the system and the embarked angular velocity for particulars cases. The advantage of the proposed compact kinematics model is that it leads to a more compact dynamic model of the CVJ.